PEMANFAATAN PUPUK KOMPOS AMPAS KELAPA DAN NPK DALAM PENINGKATAN PERTUMBUHAN TANAMAN SAWI KAILAN (Brassica oleraceae L.) - Efrina Siregar; Widya Lestari; Novilda Elizabeth Mustamu; Siti Hartati Yusida Saragih (Fakultas Pertanian, Universitas Janabadra, 2024)
Kailan mustard greens (Brassica oleraceae L.) is a horticultural plant that can be used as a family food source. This research aims to determine the effect of providing coconut dregs compost and NPK fertilizer on the growth of kailan mustard greens. The research was carried out in Ujung Bandar, Rantau Selatan, Labuhanbatu, North Sumatra. The experiment was arranged in a Randomized Block Factorial Design with the first factor being coconut dregs compost consisting of 4 levels, namely A0: control, A1: 200 g/plant, A2: 400 g/plant, A3: 600 g/plant, and the second factor was NPK which consists of 4 levels, namely N0: control, N1: 5g/plant, N2: 10 g/plant, N3: 15 g/plant. The results of the research showed that there was an interaction effect of providing coconut dregs compost and NPK on plant height, number of leaves and leaf area of kailan mustard greens. The combined dose of 600 g of coconut dregs with 15 g of NPK produced the best growth in plant height, number of leaves and leaf area of kailan mustard greens. Key words : coconut dregs;compost; fertilizer; kailan. INTISARISawi kailan (Brassica oleraceae L.) adalah tanaman hortikultura yang dapat dimanfaatkan sebagai sumber pangan keluarga. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian pupuk kompos ampas kelapa dan pupuk NPK terhadap pertumbuhan tanaman sawi kailan. Penelitian dilaksanakan di Ujung Bandar, Rantau Selatan, Labuhanbatu, Sumatera Utara. Percobaan disusun dalam Rancangan Acak Kelompok Faktorial dengan faktor pertama adalah kompos ampas kelapa yang terdiri dari 4 taraf, yaitu A0: kontrol, A1: 200 g/tanaman, A2: 400 g/tanaman, A3: 600 g/tanaman, dan faktor kedua NPK yang terdiri dari 4 taraf, yaitu N0: kontrol, N1: 5g/tanaman, N2: 10 g/tanaman, N3: 15 g/tanaman. Hasil penelitian menunjukkan adanya interaksi pengaruh pemberian kompos ampas kelapa dan NPK terhadap tinggi tanaman, jumlah daun, dan luas daun tanaman sawi kailan. Kombinasi dosis 600 g ampas kelapa dengan 15 g NPK menghasilkan pertumbuhan terbaik terhadap tinggi tanaman, jumlah daun, dan luas daun tanaman sawi kailan. Kata kunci : ampas kelapa, kailan, kompos, pupuk.